Advances in Gene Therapy Techniques to Treat LRRK2 Gene Mutation - Sun-Ku Chung; Seo-Young Lee (Biomolecules, 2022)
Leucine-rich repeat kinase 2 (LRRK2) gene mutation is an autosomal dominant mutation associated with Parkinson’s disease (PD). Among LRRK2 gene mutations, the LRRK2 G2019S mutation is frequently involved in PD onset. Currently, diverse gene correction tools such as zinc finger nucleases (ZFNs), helper-dependent adenoviral vector (HDAdV), the bacterial artificial chromosome-based homologous recombination (BAC-based HR) system, and CRISPR/Cas9-homology-directed repair (HDR) or adenine base editor (ABE) are used in genome editing. Gene correction of the LRRK2 G2019S mutation has been applied whenever new gene therapy tools emerge, being mainly applied to induced pluripotent stem cells (LRRK2 G2019S-mutant iPSCs). Here, we comprehensively introduce the principles and methods of each programmable nuclease such as ZFN, CRISPR/Cas9-HDR or ABE applied to LRRK2 G2019S, as well as those of HDAdV or BAC-based HR systems used as nonprogrammable nuclease systems.